The News illusion under surveillance? : news media credibility and media audience opinion formation process - Cayari, Laurice Christine R. 1978-; University of the Philippines Diliman College of Mass Communication (Quezon City College of Mass Communication, University of the Philippines Diliman, 2000)
The study News : Illusion Under Surveillance? aims to find out whether the present news media are still deemed credible and important by its audiences. Is the intention to inform and disseminate facts objectively still holds or details in the news already clouded with distortion and manipulation? Do audiences see media covered events as they are or do they realize that news media reality is, indeed, an illusion under surveillance? In line with this, this study also aims to know how audiences process media messages. It seeks to know how other factors such as social and personal characteristics as well as the media information itself influence their opinion of an issue. News coverage audience characteristics, opinion formation and media credibility are the four main variables that his study focuses on. News coverage was analyzed in terms of emphasis, tone and treatment of the media information/messages. Audience characteristics, on the other hand, included the media recipients' social and personal characteristics as well as their attitude and behavior toward the media, while opinion formation referred to the kind of judgment that one comes up with regarding a media covered event. Lastly, media credibility referred to the effectiveness of the media in fulfilling their social duty to inform the public as opinion free as possible. In order to come up with the desired results, the researcher employed three data gathering methods: survey, content analysis and focus interview. For the survey, a self-administered questionnaire was constructed. This survey instrument included inquiries describing the social demographics of the respondents as well as their media exposure, media reliance and how they arrive at an opinion regarding the media message and how they perceive media message credibility. For the content analysis of news reports, the content analysis guide focused on emphasis, tone and treatment of news articles and reports about crime related issues. Finally, an interview schedule looked more closely at the reliance of the informants to media information. More importantly, the interview focused on how informants evaluate media performance and and credibility as well as how they process media messages and come up with an opinion regarding it. Results of the content analysis of crime news reports revealed that different newspapers gave different levels of emphasis to crime issues, while the broadcast media gave more importance to crime issues compared to the print media. Treatment of messages was predominantly neutral whereas tone was mostly narrative/factual. Survey findings showed the dominance of TV as a source of mass information and that majority watch news everyday. Most of the respondents proved to be active and critical audiences, meaning they actively include their personal assessment in judging media information and issues. Majority, though, still highly rely on the media for social information. Nearly half, however, claimed non-reliance anymore. Lastly, it was revealed that though the news media were still deemed important, credibility, conversely, was rated negatively. Survey findings were supported by interviews. Results showed that audiences were already critical of what they watch and read. Audiences allow media influence and value media's social significance, however, they assert that the news needed improvements.
Vita.
Thesis (A.B. Communication Research)--University of the Philippines Diliman
Keywords: Press -- Philippines